Electronic structure of iron pyrite by the LMTO_ASA method - Refka Sai; Hatem Ezzaouia; Muaffaq M. Nofal (Results in Physics, 2021)
We obtain the self-consistent band structure and density of states of iron pyrite FeS2 using the linear muffin-tin orbital method in the atomic-sphere approximation (LMTO-ASA). Both the electronic structure and density of states are discussed in detail. The calculated band gap is direct, with a width of 0.90508 eV. These results agree with experimental measurements. The calculated density of states shows that the valence band is fully occupied while the first conduction band is unoccupied.